Evolution of Orthodontic Anchorage Techniques: A Comparative Analysis Using the Latent Dirichlet Allocation Algorithm - Kalkan, Ergin; Budak, Ibrahim (Scientific Scholar, 2025)
Objectives This study aims to analyze the evolution of orthodontic anchorage techniques before and after the year 2000 by utilizing the Latent Dirichlet Allocation (LDA) algorithm. The study investigates changes in treatment approaches, technological advancements, and material preferences in orthodontics. Material and Methods A comparative analysis was conducted using the LDA algorithm to examine orthodontic literature before and after 2000. The study categorized key topics and terms related to orthodontic anchorage, focusing on treatment methods, material choices, and biomechanical principles. The data were analyzed to identify shifts in treatment trends and technological developments. Results The findings indicate a transition from conventional anchorage methods, such as stainless steel wires and basic biomechanics, to more advanced skeletal anchorage systems, including mini-screws and cortical bone-supported techniques. Post-2000, the use of finite element analysis and computer-assisted treatment planning has significantly increased. Additionally, treatment approaches have shifted towards more controlled and stable mechanics, emphasizing precision in orthodontic movements. Conclusion The study highlights a significant shift in orthodontic anchorage techniques over the past decades, demonstrating the impact of technological innovations and engineering principles on treatment methodologies. The increasing reliance on skeletal anchorage and digital planning tools suggests that future advancements will continue to optimize orthodontic outcomes, improving both efficiency and patient comfort.